A 5.107-A/kg dose rate compact X-ray generator; Laser and Particle Beams; Vol. 7 pt. 4 - Filatov A. L.; Kotov Yu. A.; Mesyats G. A. Gennady Andreyevich; Sokovnin S. Yu. (1989, 1989)
В фонде НТБ ТПУ отсутствует